A TagSNP in SIRT1 gene confers susceptibility to myocardial infarction in a Chinese Han population. - Jie Cheng; Miook Cho; Jin-ming Cen; Meng-yun Cai; Shun Xu; Ze-wei Ma; Xinguang Liu; Xi-li Yang; Can Chen; Yousin Suh; Xing-dong Xiong (PLoS ONE)
SIRT1 exerts protective effects against endothelial cells dysfunction, inflammation and atherosclerosis, indicating an important role on myocardial infarction (MI) pathogenesis. Nonetheless, the effects of SIRT1 variants on MI risk remain poorly understood. Here we aimed to investigate the influence of SIRT1 polymorphisms on individual susceptibility to MI. Genotyping of three tagSNPs (rs7069102, rs3818292 and rs4746720) in SIRT1 gene was performed in a Chinese Han population, consisting of 287 MI cases and 654 control subjects. In a logistic regression analysis, we found that G allele of rs7069102 had increased MI risk with odds ratio (OR) of 1.57 [95% confidence interval (CI) = 1.15-2.16, Bonferroni corrected P (Pc) = 0.015] after adjustment for conventional risk factors compared to C allele. Similarly, the combined CG/GG genotypes was associated with the increased MI risk (OR = 1.64, 95% CI = 1.14-2.35, Pc = 0.021) compared to the CC genotype. Further stratified analysis revealed a more significant association with MI risk among younger subjects (≤ 55 years old). Consistent with these results, the haplotype rs7069102G-rs3818292A-rs4746720T containing the rs7069102 G allele was also associated with the increased MI risk (OR = 1.41, 95% CI = 1.09-1.84, Pc = 0.040). However, we did not detect any association of rs3818292 and rs4746720 with MI risk. Our study provides the first evidence that the tagSNP rs7069102 and haplotype rs7069102G-rs3818292A-rs4746720T in SIRT1 gene confer susceptibility to MI in the Chinese Han population.